Teacher Identity Discourses in Place-Exploring Discursive Resources in Pre-Service Teachers' Constructions of Teacher Identity - Johan Neander Christensson (MDPI AG, 2024)
This methodological article focuses on how to effectively map pre-service teachers' use of discursive resources in professional identity production. By adopting a discourse analytical approach, this study views identity construction as a situational, real-time process occurring in interaction. The aim is to contribute knowledge about how to systematically map and analyze the resources that pre-service teachers use to construct their teacher identities during their education. Drawing on the framework of Mediated Discourse Analysis, this article presents a model that integrates two key concepts: discourse domains, which refer to the types of discourse commonly used in teacher education, and layers of discourse, which address societal levels in identity construction. The results suggest that using these concepts to map students' use of discursive resources highlights how their knowledge of the teaching profession, their education and everyday experiences can be assets when constructing their teacher identities. While the model can be further refined and developed to better show the complexity of discursive resources in identity construction processes, it shows promise as a fruitful approach. By mapping and visualizing discursive resources through this model, this study offers valuable methodological insights into how to approach professional identity development among pre-service teachers.